Analisis Aspek Hukum Pidana dalam Menangani Kejahatan Perdagangan Narkotika Studi Kasus: Putusan Pengadilan Negeri Jakarta Selatan No.133/Pid.Sus/2023/PN JKT.SEL) - Farhan Hiola (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This article analyzes the criminal law aspects in combating drug trafficking through a case study of the verdict of South Jakarta District Court Number 133/Pid.Sus/2023/PN JKT.SEL. Juridical-normative and qualitative approaches are employed to analyze the case facts, legal arguments, sentencing considerations, and social impacts of the court's decision. Case study, descriptive, comparative, and content analysis methods are utilized to gain a comprehensive understanding of the legal and social aspects involved in addressing drug trafficking cases. The research findings provide insights into the implementation of criminal law, social influences, and countermeasures against drug trafficking crimes. Recommendations can be made for the improvement of handling similar cases in the future.